Β-defensin 3 modulates macrophage activation and orientation during acute inflammatory response to Porphyromonas gingivalis lipopolysaccharide. (April 2017) - Lyu, Jinglu; Bian, Tianying; Chen, Bin; Cui, Di; Li, Lili; Gong, Ling; Yan, Fuhua
Abstract: β-defensin 3, a multifunctional antimicrobial peptide, has immuno-regulatory activities. We investigated the modulatory mechanism of human β-defensin 3 (hBD3) on acute inflammatory response resulted from Porphyromonas gingivalis lipopolysaccharide ( P . g -LPS), which plays a pro-inflammatory role in periodontal infection and its derived systemic inflammation. P . g -LPS was administrated to mice and murine macrophages alone or along with hBD3. P . g -LPS could lead to acute inflammation as soon as 2 h. And it was observed that hBD3 significantly decreased the production of pro-inflammatory biomarkers of in response to P . g -LPS in vivo and in vitro in the early stage. Interestingly, although hBD3 as well as P . g -LPS stimulated the expression of TLR2 mRNA in macrophages in this study, hBD3 exhibited suppressive effect on the downstream NF-κB signaling pathway activated by P . g -LPS. And above all, hBD3 could polarize macrophages into M2 phenotype and this contributed to its anti-inflammatory property. These results indicated that hBD3 could have therapeutic effect on systemic inflammation associated with periodontal infections via modulating macrophage activation and orientation.